Evaluation of Cepheid’s Xpert MTB/RIF Test on Pleural Fluid in the Diagnosis of Pleural Tuberculosis in a High Prevalence HIV/TB Setting - Lusiba, John K.; Nakiyingi, Lydia; Kirenga, Bruce J.; Kiragga, Agnes; Lukande, Robert; Nsereko, Maria; Ssengooba, Willy; Katamba, Achilles; Worodria, William; Joloba, Moses L.; Mayanja-Kizza, Harriet (PLoS ONE, 2014)
Diagnosis of pleural tuberculosis (TB) using routinely available diagnostic methods is challenging due to the paucibacillary nature of the disease. Histopathology and pleural tissue TB culture involves an invasive procedure which requires expertise and appropriate equipment, both often unavailable in many health units. Xpert MTB/Rif test has been widely evaluated in sputum specimens but data on its performance in pleural TB is scarce. We evaluated the accuracy of Cepheid’s Xpert MTB/Rif test on pleural fluid in the diagnosis of pleural TB in Uganda. Methods: Consenting adult patients with exudative pleural effusions underwent pleural biopsy and the tissue obtained subjected to Lowenstein-Jensen and mycobacterial growth indicator tube MTB cultures and histopathology. Pleural fluid for Xpert MTB/Rif testing was also collected. Data on socio-demographic characteristics, clinical symptoms, HIV status and CD4 count were also collected. Sensitivity, specificity, positive and negative predictive values of Xpert MTB/Rif test on pleural fluid in pleural TB diagnosis were calculated using pleural tissue MTB culture and/or histopathology as the reference standard. Results: Of the 116 participants [female 50%, mean age 34 (SD 613], 87/116 (75%) had pleural TB confirmed on pleural tissue culture and/or histopathology. The Xpert MTB/Rif test identified 25 (28.7%) of the 87 confirmed pleural TB cases. The sensitivity and specificity of Xpert MTB/Rif test were 28.7% and 96.6% respectively while the positive and negative predictive values were 96.1% and 31.1% respectively. Conclusion: Xpert MTB/Rif test on pleural fluid does not accurately diagnose pleural TB and therefore cannot be used as an initial evaluation test in patients with suspected pleural TB. New, rapid and accurate tests for the diagnosis of pleural TB are still warranted.
Keywords: Evaluation; Cepheid’s Xpert MTB/RIF Test; Pleural Fluid; Pleural Tuberculosis